Possibility of ANFIS application for evaluation roughness of surface during cnc machining - Jovanović, Milovoje; Jović, Srđaj (Journal of Production Engineering, 2023)
In this investigation was analyzed the surface roughness of Co29Cr6Mo medical alloy which is machines with a CNC machine. The method of ANFIS (adaptive neuro fuzzy inference system) was applied to estimate important factors of roughness of surface of the material during machining process. Than main goal was to evaluate the machining parameters for the surface roughness in order to optimize the machining process for the best conditions. Four machining parameters are considered. Average surface roughness Ra is considered as output since it is the only relevant measure of the surface quality.